2001
DOI: 10.1086/318944
|View full text |Cite
|
Sign up to set email alerts
|

Optical Classification of Southern Warm Infrared Galaxies

Abstract: In this paper, we present high-resolution optical spectra and optical classiÐcations from our large sample of 285 warm infrared galaxiesWe have classiÐed these galaxies using new 108 \ L IR \ 1012.5 L _ . theoretical lines on the standard optical diagnostic diagrams. We use a theoretical extreme mixing line between the starburst and AGN regions to classify LINER galaxies and we deÐne a theoretical boundary separating AGNs from starbursts. We Ðnd that many galaxies previously classiÐed as LINERs appear to lie o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
612
3
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 442 publications
(643 citation statements)
references
References 90 publications
25
612
3
3
Order By: Relevance
“…Firstly, in Kewley et al (2001), we have shown that the optical diagnostic diagrams are extremely sensitive to the presence of an AGN. An AGN that contributes only 20% to the optical emission increases the line ratios sufficiently that it would be classiÐed as an AGN.…”
Section: The Observational Comparison Samplementioning
confidence: 98%
See 2 more Smart Citations
“…Firstly, in Kewley et al (2001), we have shown that the optical diagnostic diagrams are extremely sensitive to the presence of an AGN. An AGN that contributes only 20% to the optical emission increases the line ratios sufficiently that it would be classiÐed as an AGN.…”
Section: The Observational Comparison Samplementioning
confidence: 98%
“…Spectra were obtained in the red and blue wavelength ranges using the Double Beam Spectrograph on the Mount Stromlo and Siding Springs 2.3 m telescope. Full details of our observations are discussed in Kewley et al (2000Kewley et al ( , 2001. All 225 objects were classiÐed into AGN, starburst, and LINER types using new theoretical classiÐcation lines on the VO87 diagnostic diagrams.…”
Section: The Observational Comparison Samplementioning
confidence: 99%
See 1 more Smart Citation
“…A classification scheme using optical emission line ratios was first put forward by Heckman (1980) and subsequently amendments have been proposed by, inter alia, Baldwin et al (1981), Kewley et al (2001Kewley et al ( , 2006 and Kauffmann et al (2003a). In this research, a two-pronged approach was adopted to identify LINERs.…”
Section: Diagnostic Tests To Select Linersmentioning
confidence: 99%
“…Arp 161 is a compact HII galaxy (Kewley et al (2001)) with a faint optical fan to the southwest with a length of ∼ 45 " (16.2 kpc) (Fig. 22).…”
Section: Arp 161mentioning
confidence: 99%